Analysis The Use of Social Media On Purchase Decisions - Rahmat Alfikri (Jurnal Bisnis dan Manajemen, 2021)
The purpose of this research is to analyze the extent to which social media users influence purchasing decisions in small and medium enterprises in the city of Pontianak with marketing dimensions in the form of Online Communities, Interaction, Content Sharing, Accessibility, Credibility on purchasing decisions through social media. SME consumers in Pontianak were taken as respondents. This research uses an accidental simple random sampling technique; the number of respondents collected, 100 respondents. Data analysis using Structural Equation Modelling (SEM). The results showed that the marketing dimension had a direct effect on purchasing decisions through social media. Suggestions in this study are for business people to be more creative and innovative in making new strategies, so as to create and influence purchasing decisions.